Circular economy and sustainable agriculture ecosystems a case of hybrid paper mulberry in the Yellow River Basin, China - Lan Le; V. Ratna Reddy; Jianjun Jin; Dil B. Rahut (Discover Sustainability)
Abstract HPM is a woody forage crop that has the potential to strengthen the agriculture ecosystems, as it can be grown on waste and degraded lands under varying climatic conditions. It is economically viable and profitable. Despite the promotional initiatives, farmers response has been lukewarm in expanding the area under HPM. This paper examines the economic as well as non-economic reasons behind the farmers decisions of adoption and dis-adoption of HPM plantations in the Yellow River Basin of China. The analysis is based on the field survey covering 485 sample households, 4 processing industries and 38 end users of HPM products spread over three counties in two provinces of the Yellow River Basin, China. The analysis brought out clearly that though economic reasons like low returns at the farmer level are important, non-economic reasons like land constraints and social restrictions are also equally, if not more, important in explaining the farmers decisions of low adaptation of HPM plantings. Interestingly, farmers are not inclined to accept compensation for planting HPM. The reasons include: risks associated with planting, lack of family labour and high investment costs. Thus, non-economic factors appear to be important in explaining the farmers decisions. The analysis suggests a failure in translating and transferring the research findings and policy initiatives to farm level. Besides, some of the contradictions observed at the field level also vindicate the gap between ‘lab to land’ and ‘policy to practice’.